Clinical and radiographic effectiveness of statins in the treatment of periodontitis - Heber Isac Arbildo Vega; Víctor Alay Baca; Victoria Vanessa García Moreno; Tania Belú Castillo Cornock; Gustavo Alfredo Alberto Giribaldi Ugáz; Hernán Vásquez Rodrigo (Editorial Ciencias Médicas, 2021)
Introduction: Periodontal disease is a chronic multifactorial infectious inflammatory condition characterized by inflammation of soft periodontal tissue. In advanced stages (periodontitis) it causes progressive destruction of hard periodontal tissue, leading to eventual tooth loss if not treated. Objective: Determine the clinical and radiographic effectiveness of statins in the treatment of periodontitis. Methods: A search was carried out in the literature published until April 2019 in the biomedical databases PubMed, Embase, SciELO, Science Direct, Scopus, System for Information on Gray Literature in Europe, Latin American and Caribbean Health Sciences Literature, Google Scholar, and Cochrane Central Register of Clinical Trials. The following selection criteria were defined for the studies: randomized clinical trials published in the last five years and reporting on clinical and radiographic effects (probing depth, clinical insertion level, plaque index, bleeding index, gingival index, intraosseous defect and defect depth) of statins in the treatment of periodontitis. Bias risk analysis was based on the Cochrane manual of systematic reviews of interventions. Results: A total 19 papers were retrieved, of which 100% reported differences in the probing depth, clinical insertion level, plaque index, bleeding index, gingival index, intraosseous defect and defect depth of statins in the treatment of periodontitis. Conclusions: The literature review conducted suggests that the use of statins is clinically and radiographically effective in the treatment of periodontitis.